Infusing Environmental Studies in the Undergraduate Curriculum of a Home Science Program: A Pedagogical Intervention - Muralidhar, Adithi; Sayyed, Huda; Pandurang, Mala (Voices of Teachers and Teacher Educators, 2023)
Environmental Studies (ES) is an important theme that features all through school education and also finds a place at the undergraduate level. However, the implementation of the ES curriculum at the undergraduate level is largely done in a theoretical and pedantic manner. Moreover, the theme may also lack relevance for students who are pursuing degrees that may not seemingly or directly be related to the environment. In order to address these issues, an intervention was designed collaboratively between the institutional stakeholders; and implemented in a college of home science. This article reports the various aspects of the intervention undertaken as well as the insights gained from students’ feedback. Recommendations to enhance the intervention are presented at the end.